2011
DOI: 10.1016/j.jval.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Population-Based Values for EQ-5D Health States in Thailand

Abstract: Values for EQ-5D health states were estimated from the Thai general population. This is the first Thai generic health state value results to be used in evaluating health interventions in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 26 publications
3
110
1
Order By: Relevance
“…Countries included in the analysis were: Argentina, Belgium, China, Denmark, England, Finland, France, Germany, Greece, Hungary, Italy, Korea, the Netherlands, New Zealand, Slovenia, Spain, Sweden, Thailand, United Kingdom, and the United States [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For two countries (Argentina and China), the dataset transfer to the central archive was not possible.…”
Section: Datamentioning
confidence: 99%
“…Countries included in the analysis were: Argentina, Belgium, China, Denmark, England, Finland, France, Germany, Greece, Hungary, Italy, Korea, the Netherlands, New Zealand, Slovenia, Spain, Sweden, Thailand, United Kingdom, and the United States [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For two countries (Argentina and China), the dataset transfer to the central archive was not possible.…”
Section: Datamentioning
confidence: 99%
“…The EQ-VAS of Thai patients after heart surgery (0.84 in Table 2) was higher than that of the Thai general population (0.77) [13] (P < 0.01). However, it should be noted that the mean age of the general Thai population (44.6 years) and the percentage of males (45.7%) [13] were lower than those of the Thai patients after heart surgery (mean age = 50.4 ± 13.7 and male = 49.5%). Generally, younger male people tended to have a higher HRQoL than older women.…”
Section: Health Utilitymentioning
confidence: 78%
“…Table 5. Analysis of EQ-5D, EQ-VAS, Physical and Mental Component Summary scores based on patient characteristics Characteristic n = 386 EQ-5D EQ-VAS PCS MCS mean ± ± ± ± ± SD mean ± ± ± ± ± SD mean ± ± ± ± ± SD mean ± ± ± ± ± SD The patients had the marginally lower EQ-5D utility score, but slightly higher EQ-VAS score than those of the Thai general population [13]. This finding confirmed that their HRQoL corresponded to those of the general Thai population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations